2014
DOI: 10.1123/pes.2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physical Fitness and Sports Participation Among Children With Different Levels of Motor Competence: A 2-Year Longitudinal Study

Abstract: The goal of this study was to investigate differences in physical fitness and sports participation over 2 years in children with relatively high, average, and low motor competence. Physical fitness and gross motor coordination of 501 children between 6-10 years were measured at baseline and baseline+2 years. The sample compromised 2 age cohorts: 6.00-7.99 and 8.00-9.99 years. An age and sex-specific motor quotient at baseline testing was used to subdivide these children into low (MQ < P33), average (P33 ≤ MQ <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
69
0
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 20 publications
15
69
0
14
Order By: Relevance
“…The low-motor competence group performed worse on the standing long jump and 50-m run test compared with the high-motor competence group in each year of the follow-up study. Similar results were found in a 2-year follow-up study in 501 children of different levels of motor competence, aged between 6 and 10 years [14]. The high-motor competence group outperformed their low-levelled counterparts in several physical fitness tests, including the standing broad jump.…”
Section: Introduction ▼supporting
confidence: 84%
“…The low-motor competence group performed worse on the standing long jump and 50-m run test compared with the high-motor competence group in each year of the follow-up study. Similar results were found in a 2-year follow-up study in 501 children of different levels of motor competence, aged between 6 and 10 years [14]. The high-motor competence group outperformed their low-levelled counterparts in several physical fitness tests, including the standing broad jump.…”
Section: Introduction ▼supporting
confidence: 84%
“…There are several studies which have analysed associations between the degree of motor coordination and sports participation [7][8][9][10]. In general, these previous findings have indicated a positive correlation between motor coordination and sports participation.…”
Section: Introductionmentioning
confidence: 59%
“…These data illustrate the physical illiteracy of the next generation of aspiring Olympic athletes. In support of this contention, a 2-year investigation of 501 children between 6 and10 years of age found that low motor competent children participated less in sports and had fewer opportunities for developing motor abilities and physical fitness 28. Consequently, the growing number of children with low muscle strength and poor motor skills within the general population is likely to reduce the talent pool from which national governing bodies and professional sports organisations can recruit their next generation of elite athletes.…”
Section: Slower Lower and Weakermentioning
confidence: 99%